Pemanfaatan Biomassa dan Limbah Peternakan untuk Pembutan Pupuk Organik Berasam Humat Tinggi - Hidayah, Fitria Fatichatul (Prosiding KPSDA, 2015)
Fertilizers used by farmers today isÂ  artificial fertilizers (inorganic). The use of artificial fertilizer would cause the soil structure damaged due to artificial fertilizer will only provide nutrients to plants without regard to the soil fertility. Finally, food productivity will decrease and food security will be so weak. To overcome this, there needs to be a good fertilizer that meets nutrient for plants and soil. To overcome this, a good fertilizer that meets nutrient for plants and soil is very necessary. The use of biomass and farm waste to increase the value of agricultural wastes is so potential to be organic fertilizer. Composting organic materials can produce humic acid. Humic acid is able to absorb nutrients from the environment exploited by plant roots and transferred into the root cap. The purpose of study is to produce humic acid from agricultural and livestock waste. The method of this study is the extraction. Stages of this study are preparation, composting, humic acid isolation, and purification of humic acid. The results of this study showed the highest levels of humic acid is 48.08%.